2020
DOI: 10.1039/c9cc08130e
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry reveals the assembly pathway of encapsulated ferritins and highlights a dynamic ferroxidase interface

Abstract: Encapsulated ferritins assemble into an annular decamer structure via an iron-dependent assembly pathway where dimers associate to form the ferroxidase active site.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…[4] Ty pically,the gene encoding for Enc is located in atwo-gene operon with either ferritin (Flps) or hemerythrinslike proteins,o rd ye-decolorizing peroxidases (DyPs). [2,9] Selective packaging of co-expressed proteins is promoted by ac onserved amino-acid sequence (encapsulin localization sequence,E LS) at their C-terminus. [10][11][12] Importantly,n onnative cargo proteins can be directed inside Enc via simple tagging with ELS,e nabling self-assembly of the new functional compartment.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Ty pically,the gene encoding for Enc is located in atwo-gene operon with either ferritin (Flps) or hemerythrinslike proteins,o rd ye-decolorizing peroxidases (DyPs). [2,9] Selective packaging of co-expressed proteins is promoted by ac onserved amino-acid sequence (encapsulin localization sequence,E LS) at their C-terminus. [10][11][12] Importantly,n onnative cargo proteins can be directed inside Enc via simple tagging with ELS,e nabling self-assembly of the new functional compartment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the absence of cargo proteins, M. xanthus encapsulins form both T = 1 and T = 3 particles, but in the presence of the cargo, only T = 3 particles are formed [ 48 ]. On the other hand, Ross et al observed dimeric H. ochraceum FLPs in the absence of Fe +2 , suggesting that FLPs can also adopt different oligomeric states [ 56 ]. Interestingly, s-FLPs were initially classified as non-encapsulated FLPs since they lack a TP in their C-termini [ 57 ].…”
Section: Encapsulated Flpsmentioning
confidence: 99%
“…For example, ΔG is −7.8 kcal/M and −34.1 kcal/M for the A–A and B–B interfaces, respectively, of H. ochraceum EncFtn (Hoch_EncFtn, calculated by PISA, from the crystal structure PDB ID: 5n5f [ 28 ]). Ross et al performed an in-depth analysis of the Hoch_EncFtn pentamers of dimers assembly pathway using native mass spectrometry and hydrogen-deuterium exchange mass spectrometry [ 56 ]. Their analysis shows that decameric assembly formation is iron dependent and it is associated by the addition of the non–FOC dimers via the formation of the FOC interface upon iron binding.…”
Section: Encapsulated Flpsmentioning
confidence: 99%
“…Applications of non-denaturing MS, often referred to native MS, are increasingly being used to investigate non-covalently bound protein cofactors, simple protein-protein complexes, or multi-protein super complexes [42,43]. Amongst studies of protein-cofactor interactions are an increasing number on proteins that contain metallo-cofactors [2,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. These have been particularly insightful where there is chemistry taking place at the cofactor, owing to the unique capability of native MS to simultaneously measure the accurate mass of multiple species, which may be different forms of the same protein, present in solution.…”
Section: Introductionmentioning
confidence: 99%